Determinasi Audit Report Lag: Peran Kepemilikan Institusional, Auditor Switching, dan Kompleksitas Audit dengan Moderasi Ukuran Perusahaan - Putra, Rudi Syaf; Armel, R Septian; Suci, Rama Gita; Fionasari, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2026)
In consumer cyclicals entity listed on the Indonesia Stock Exchange for the period of 2021–2024, this study intends to examine the impact of institutional ownership, auditor turnover as well as audit complexity on audit report latency, with company size serving as a moderating variable. A quantitative approach is utilised in the present study using the logistic regression method. The publicly available financial records and annual reports of the company were the sources of the research data. While audit complexity and institutional ownership had no effect on audit report delays, studies demonstrate that auditor switching does. Also, the moderation test shows that there is no effect of firm size on the correlation between audit report lag and institutional ownership, auditor change, or audit complexity.